2019
DOI: 10.1002/stc.2472
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Bragg grating sensors for subgrade deformation monitoring in seasonally frozen regions

Abstract: Summary Excessive subgrade permanent deformation resulting from heavy vehicle traffic and freezing–thawing cycles is one of the primary causes of road damage in seasonally frozen regions. In this paper, an implanted cantilever sensing beam based on fiber Bragg gratings (FBGs) is proposed for subgrade deformation monitoring. Two optical fibers with inscribed FBGs were adhered to the opposite external sides of a PVC pipe which was selected as substrate. After laboratory calibration tests, the cantilever sensing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Realizing field tests concerning the application of Fiber Bragg Grating sensors is of crucial importance for the monitoring of both railways [10,11] and roads [12][13][14]. Even though research regarding fiber-based weigh-in-motion systems has been reported over the last 20 years, none of these references offer a quantitative analysis about weight measurements in the form of a final product that conforms to transportation regulations [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Realizing field tests concerning the application of Fiber Bragg Grating sensors is of crucial importance for the monitoring of both railways [10,11] and roads [12][13][14]. Even though research regarding fiber-based weigh-in-motion systems has been reported over the last 20 years, none of these references offer a quantitative analysis about weight measurements in the form of a final product that conforms to transportation regulations [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The spectral width of the grating period Λ is in the range 0.05–0.3 nm, and all other ordinary light passes through the optical fiber grating [ 23 ]. The Bragg wavelength λ B satisfies Bragg conditions [ 24 ]: where is the effective refractive index of the optical fiber core.…”
Section: Operational Principlesmentioning
confidence: 99%
“…This is largely related to the greater availability and relative cheapness of equipment that registers physical signals from these sensors. The advantages of FOSS based on Bragg gratings and typical schemes for their application are widely covered in the literature, in particular in previous papers 1–4 . In a number of works, the results of measurements recorded with FOSS based on Bragg gratings are compared with data obtained by other strain measurement systems 5–8 …”
Section: Introductionmentioning
confidence: 99%
“…The advantages of FOSS based on Bragg gratings and typical schemes for their application are widely covered in the literature, in particular in previous papers. [1][2][3][4] In a number of works, the results of measurements recorded with FOSS based on Bragg gratings are compared with data obtained by other strain measurement systems. [5][6][7][8] It is necessary to have estimates of the reliability of the strain measurement results when using any sensors, including FOSS based on Bragg gratings.…”
Section: Introductionmentioning
confidence: 99%